Profil Kemampuan Berpikir Kritis dan Kreatif Siswa SMA Pada Materi Energi Terbarukan: - - Aminingsih, Amilia; Khoiri, Nur; Nuroso, Harto; Hayat, Muhammad Syaipul (PendIPA Journal of Science Education, 2024)
Critical and creative thinking skills at SMA Pangudi Luhur (PL) Don Bosko are still classified as moderate critical thinking and less creative thinking, respectively. This illustrates that some students have not been able to interpret information scientifically and develop ideas to solve a problem. This study aims to analyze students' critical and creative thinking skills in understanding renewable energy material at SMA PL Don Bosko. These skills are important to face global challenges related to sustainable energy utilization. The research method used is descriptive with quantitative and qualitative approaches. Data were obtained through tests and questionnaires involving 20 students as respondents. The results of the analysis show that most students have critical thinking skills in the moderate category with an average achievement percentage of 62.94%, with the most dominant aspect of Elementary Clarification. However, students' creative thinking skills are still classified as lacking with an average achievement of 63.8%, with dominant results in the fluency aspect. Factors such as learning approaches, active student involvement, and learning resource support influence the development of these skills. This study suggests integrating a project-based learning model to improve students' critical and creative thinking skills on renewable energy materials.